Time variation of fundamental constants in nonstandard cosmological models - Mosquera, Mercedes Elisa (2017)
In this work we have studied the lithium problem in nonstandard cosmological models. In particular, by using the public code ALTERBBN, we have included in the computation of the primordial light nuclei abundances, the effects of the inclusion of dark energy and dark entropy, along with the variation of the fine structure constant and the Higgs vacuum expectation value. In order to set constrains on the variation of the fundamental constants we have compared our theoretical results with the available observational data. We have found that the lithium abundance is reduced for not-null variation at the 3σ-level of both constants.